Resepsi Bacaan Ghorib Isymam Riwayat Hafs dalam Tradisi Living Qur'an: Studi pada Pondok Pesantren Maritim Tuban - Muhammad Suryo Prawibowo; Azibur Rahman (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to analyze the practice of Ghorib Isymam recitation in the Hafs narration within the tradition of a coastal Islamic boarding school and to explore students' understanding, perceptions, and experiences from the perspective of Living Qur'an. The research employed a qualitative approach using a case study design at Pondok Pesantren Maritim Tuban. Data were collected through participant observation, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that Isymam recitation is understood not merely as a technical rule of qira'at, but also as a symbol of scholarly depth, the continuity of Qur'anic transmission (sanad), and the religious identity of the students. Learning through talaqqi and musyafahah methods fosters religious experience, discipline, accuracy, and respect for teachers as part of the transmission of Qur'anic knowledge. Furthermore, the practice strengthens collaborative learning and represents how the Qur'an is lived within the educational culture of the pesantren. This study contributes to the development of Living Qur'an studies by demonstrating that Qur'anic reception is manifested not only in religious rituals but also in the technical practice of qira'at, which embodies social, spiritual, and educational dimensions within the pesantren tradition.